Controversies in Archaeology by Alice Beck Kehoe - Jett, Stephen C. (Journal of Scientific Exploration, 2013)
Anthropologist/archaeologist Alice B. Kehoe not only has a solid record of empirical research and scholarly publication but is also known for her critiques of American archaeology and archaeologists (notably, Kehoe 1998, in which she does not shrink from calling spades spades). Further, certain of her interests and ideas have involved some of the most contentious topics in the field. Thus, she is a "natural" as author of a book on Controversies in Archaeology. This particular volume is aimed at college-level courses but is also informative for a broader audience. It tells much more than what is or has been controversial; it gives extended glimpses of many general changes that have occurred in anthropology's subfield of archaeology over the past half-century or more. Numerous case studies are provided. A major point is that differing values and presuppositions among archaeologists and others commonly lead to differing and often conflicting interpretations of the data and even to divergent opinions as to what data are looked for and at.